Does Attribute Framing Exist in Audit Decision Aid? - Dovi Septiari; Goedono Goedono (Universitas Muhammadiyah Yogyakarta, Indonesia, 2019)
This study aims to test the framing effect in audit decision aid. The research employs a between-subject experimental design involving 56 undergraduate students as the sample. The dependent variable is the tendency to follow the aid recommendation which is measured using Gomaa, Hunton, Vaassen, and Carree's (2011) scenario. Framing effect is manipulated as follows: (1) positive framing, (2) negative framing. The result shows that framing effect exists in audit decision aid, especially, in how the aid reliability presented (positive or negative) influences the final participant's decision. This research seeks to contribute to the development of framing theory, particularly to test the framing phenomena in audit decision aid. Previous studies on this realm focus on health, politic, finance, business, and marketing areas and only a few studies are found discussing this issue in the auditing area. The result would also be useful in the practical field where it should now be obvious that an auditor should never be over-reliant on decision aid. Decision aid can indeed make decision bias if the auditor thinks using only the aid is enough to make a decision and forgets to use professional judgment. The result of the study gives a warning to auditors that the way information on the reliability of a decision aid is presented can make a decision bias.